Aurell, Jaume, What Is a Classic in History?: The Making of a Historical Canon, Cambridge, Cambridge University Press, 2024, 342p. ISBN: 978-1-009-46995-1. 30,33€ - Manel García-Sánchez (Memoria y Civilización)
Book Review